Coercive dual-class exchange offers - Ruback, Richard S. (Journal of Financial Economics, 1988)
Dual-class exchange offers give stockholders the oppurtunity to exchange common stock for shares with limited voting rights but higher dividends. This paper develops a model to analyze the exchange decision. It shows that exchange offers can induce outside shareholders to exchange their shares for limited voting shares even though the same shareholders, in the same circumstances but acting collectively, would choose not to exchange.